Manajemen Strategi pada Organisasi Pemerintahan Jawa Timur Sebuah Pendekatan "Fish Schale Multiscience" - Wijayati, Dewie Trie (Jurnal Aplikasi Manajemen, 2009)
Strategic management is considerably required by the government organizations in order to attain prosperity that could be translated through giving a good service and satisfaction to the society. The researcher utilized "Fish Schale Multi-science" approach and proposes three variables to define strategic management applications of East Java government organizations. These variables are authority, leadership, and commitment. 220 respondents from 37 organizations; from the agencies, institutions, and offices have chosen as the sample of this research. Structural Equation Modeling (SEM) being utilized as the research analysis to clarify the correlation between the variables. Proposed model analysis is based on the "Fish Schale Multi-science" approach. Based on the research result, researcher concludes that strategic management implementation of East Java Government organization is still poor on improving its public services. It is due to centralized authoritative bureaucracy and directive leadership. Furthermore, it also found that the evaluation pose as the most prominent step in strategic management application in East Java Government Organization.